Pemanfaatan Bead Alga Chlorella Sp. Untuk Menyisihkan Total Suspended Solid (TSS) Pada Limbah Cair Sawit Menggunakan Flat-Fotobioreaktor - Darmayanti, Indah; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm oil mill effluent containing pollutants such as organic matter and high suspended solids that contributes to environmental pollution. Organic material contained in palm oil mill effluent can be used as nutrition by microalgae Chlorella sp. which is entrapped inside the alginate bead and can reduce TSS content in palm oil mill effluent. The TSS removal process was carried out in a flat-photobioreactor with various concentrations of algal bead in the amount of 6, 8, 10, 12, and 14 beads/mL of wastewater with contact times of 0, 1, 3, 5, and 7 days. Based on the results of the study, the best TSS removal efficiency was found in flatphotobioreactors with concentrations of algal bead 12 beads/mL of wastewater on the seventh day at 80.1%. Keywords: Palm Oil Mill Effluent, Chlorlla sp., Algal bead concentration, TSS